2023
DOI: 10.1099/mic.0.001354
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cyclic di-GMP signalling on a short and long term time scale

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 179 publications
2
5
0
Order By: Relevance
“…Pflu0185 is a regulatory protein composed of two enzymatic domains: a diguanylate cyclase (DGC) -responsible for the synthesis of cyclic-di-GMP (c-di-GMP) -and a phosphodiesterase (PDE)responsible for breakdown of c-di-GMP [49]. In P. aeruginosa functional analysis shows the protein to have PDE function, but no DGC activity [8], which is consistent with the genetic analysis reported here.…”
Section: Local Hyper-mutability Underpins Lineage Adaptationsupporting
confidence: 84%
“…Pflu0185 is a regulatory protein composed of two enzymatic domains: a diguanylate cyclase (DGC) -responsible for the synthesis of cyclic-di-GMP (c-di-GMP) -and a phosphodiesterase (PDE)responsible for breakdown of c-di-GMP [49]. In P. aeruginosa functional analysis shows the protein to have PDE function, but no DGC activity [8], which is consistent with the genetic analysis reported here.…”
Section: Local Hyper-mutability Underpins Lineage Adaptationsupporting
confidence: 84%
“…There may also be other factors that act to inhibit EmaS in the wild-type strain, which could result in higher expression of P emaS in ∆emaS compared to the wild type. A similar scenario has been observed in P. aeruginosa, where it was found that the regulatory protein HapZ interacts with the REC domain of the sensor protein SagS when bound to cyclic di-GMP, thereby inhibiting phosphate transfer between SagS and downstream proteins [26]. Through SMART (Simple Modular Architecture Research Tool) analysis of its secondary structure, we found that the sensor protein EmaS also possesses a REC domain within its C-terminal structure, which can receive signals from sensor proteins and bind with DNA.…”
Section: Kinetic Characterization Of Dj41_2796supporting
confidence: 70%
“…Binding of cyclic di-GMP to the elongation factor P facilitates translation of proline tracks in biofilm proteins and to the α-L-glutamate ligase RimK stimulates its enzymatic activity leading to C-terminal glutaminylation of the ribosomal protein RpsF to modulate translation (Guo et al, 2022;Little et al, 2016). On the overall evolutionary time scale equally as the cyclic di-GMP network encoded by genomes, cyclic di-GMP binding sites of individual proteins can rapidly appear and disappear in evolution (Römling, 2023).…”
Section: Iver S It Y and Pl A S Ti Cit Y Of C Yclic Di-g Mp Recep Tor Smentioning
confidence: 99%
“…Cyclic di-AMP signaling seems to have been diminished almost entirely in many phyla though, predominantly in alpha-, beta-, and gamma-proteobacteria. Equally, but by far less frequently, cyclic di-GMP signaling has been reduced or entirely disappeared rapidly in evolutionary terms within Pseudomonadota (previously proteobacteria) and other phyla (Liu et al, 2020;Ojha et al, 2021;Römling et al, 2023). This evolutionary flexibility is remarkable with the number of cyclic di-GMP turnover proteins to span from 0 to 86 for a genome of even minor size within a phylum (http://www-ncbi-nlm-nih-gov.proxy.kib.ki.se/Compl ete_Genom es/c-di-GMP.html).…”
Section: Yclic Di-g Mp a S A Ub I Qu Itous Life S T Yle Reg Ul Ator I...mentioning
confidence: 99%